Impacts of Betaine Addition in Sow and Piglet's Diets on Growth Performance, Plasma Hormone, and Lipid Metabolism of Bama Mini-Pigs - Cheng, Yating; Song, Mingtong; Zhu, Qian; Azad, Md. Abul Kalam; Gao, Qiankun; Kong, Xiangfeng (Frontiers in Nutrition, 2021)
The present study evaluated the effects of betaine addition in sow and piglet’s diets on growth performance, plasma hormone, and lipid metabolism of Bama mini-pigs. A total of 26 pregnant Bama mini-pigs and 104 weaned piglets were selected and divided into different dietary treatment groups (details in “Materials and methods”). The blood and muscle samples were collected at 65-, 95-, and 125-day-old, respectively. The results showed that betaine addition in sow-offspring diets increased (P < 0.05) the body weight, average daily gain, and average daily feed intake at different stages of pigs compared with the control group. Betaine addition in sow-offspring diets increased (P < 0.05) the plasma gastrin level at 95-day-old, while betaine addition in sow diets decreased (P < 0.05) the plasma peptide YY and leptin levels at 65-day-old pigs. In the medium- and long-chain fatty acids content analysis, betaine addition in sow-offspring diets decreased (P < 0.05) the C10:0 content at 65-day-old and C18:1n9t content at 125-day-old, while increased (P < 0.05) the C24:0 content at 125-day-old in the longissimus dorsi muscle of pigs. In biceps femoris muscle, contents of C12:0 at 65-day-old, C11:0 at 95-day-old, and C20:4n6 at 125-day-old were decreased (P < 0.05) after the betaine addition in both sow and piglet’s diets. In addition, betaine addition in sow diets decreased (P < 0.05) the C20:0 content at 125-day-old, while betaine addition in sow-offspring diets increased (P < 0.05) the C18:3n6 and decreased C24:0 contents at 65-day-old pigs. In psoas major muscle, betaine addition in sow and sow-offspring diets decreased (P < 0.05) the contents of C18:1n9t at 65-day-old and C20:1 at 95-day-old, while betaine addition in sow diets decreased (P < 0.05) the intramuscular fat content at 125-day-old. Moreover, betaine addition was also associated with muscle lipid deposition and metabolisms by regulating the gene expressions related to fatty acid metabolism. These findings suggested that betaine addition in sow and sow-offspring diets could improve the growth performance and lipid quality by altering plasma hormone level and fatty acid composition and regulating gene expressions related to fatty acid metabolism.